2018
DOI: 10.1371/journal.pone.0206482
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreflective foci on optical coherence tomography associate with treatment outcome for anti-VEGF in patients with diabetic macular edema

Abstract: PurposeTo investigate the relationship between baseline number of hyperreflective foci (HF) on spectral domain optical coherence tomography (SD-OCT) in patients with diabetic macular edema (DME), as well as the dynamics of HF during treatment with anti-vascular endothelial growth factor (VEGF), and treatment response.MethodsWe evaluated patients diagnosed with DME scheduled for treatment with intravitreal bevacizumab. Eyes were classified as adequate or insufficient treatment responders based on logMAR visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 29 publications
6
81
0
2
Order By: Relevance
“…The potential clinical relevance of HF was demonstrated in previous studies showing that HF may be a predictor of treatment response to intravitreal anti–vascular endothelial growth factor or corticosteroid therapy in DME. 20 , 22 In the current study, we observed significantly higher numbers of HF in all stages of DME versus patients without DME. The number of HF was especially high in severe DME, suggesting the presence of a strong link between HF and exudative retinal disease.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The potential clinical relevance of HF was demonstrated in previous studies showing that HF may be a predictor of treatment response to intravitreal anti–vascular endothelial growth factor or corticosteroid therapy in DME. 20 , 22 In the current study, we observed significantly higher numbers of HF in all stages of DME versus patients without DME. The number of HF was especially high in severe DME, suggesting the presence of a strong link between HF and exudative retinal disease.…”
Section: Discussionsupporting
confidence: 58%
“…We further substantiated the relationship between HF and disease activity by the correlation we found between HF and visual acuity, in consistence with previous reports. 17 , 20 , 26 The occurrence of HF in diabetic patients may act as an early warning sign for oncoming vision loss. The exact nature of the relation of HF and visual acuity is yet unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also assessed CST and macular morphology via OCT (Cirrus High-Definition OCT; Carl Zeiss Meditec, Dublin, CA, USA), and the axial length was measured using an IOL Master instrument (Carl Zeiss Meditec). We used a horizontal B-scan OCT image centered on the fovea for measuring hyperreflective foci (HF) and total length of ellipsoid zone (EZ) disruption within the central 3000 μm around the fovea [20,21]. We evaluated changes in CST at the 1-month visit after three consecutive monthly intravitreal bevacizumab (IVB) injections.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Eine weitere Theorie beschreibt diese Foci als degenerierte Photorezeptorzellen [11]. In einer aktuellen multizentrischen Studie wurden diese HF untersucht und als möglicher Biomarker für den Erfolg der Anti-VEGF-Therapie und der Sehprognose eingestuft [12]. [14].…”
Section: Hyperreflektive Foci (Hf)unclassified